Guidelines for Software Acquisition - Bhat, P.K.; Kewlani, J.C (DESIDOC Journal of Library & Information Technology, 2002)
Computer users require software for Specific applications but are sometimes un-able to decide as to whether they should go in for its in-house development or acquisition From external sources. And in case a decision is taken to buy the software, how should they go about the task? This article endeavours to answer such questions for the guidance of a user in respect of various steps in software acquisition, viz. feasibility study, market exploration, software selection .process, vendor selection, benchmarking, etc. The suggestions made are based primarily on then-in-use high-level languages, assembler, the long experience of the authors in the area system and a limited range of specific of computer software.